Brain Tumors An Update - Agrawal, Amit; Rafael Moscote-Salazar, Luis (IntechOpen, 2018)
We all know that the field of neuro-oncology is heterogeneous and under continuous development with the addition of new knowledge and information on a regular basis. The present book "Brain Tumor - An Update" is an attempt to share the personal experiences of experts who are involved in neuro-oncology-related research. Through this book, the authors share their experiences and provide details about the pathophysiology, neuroimaging approaches, and management options, and how to go about decision-making in patients with brain tumors. We hope that the valuable contributions from the authors shall facilitate understanding about brain tumors. I am grateful to all the authors who have contributed their tremendous expertise, and I would like to acknowledge the outstanding support of Ms. Danijela Sakic, Author Service Manager, IntechOpen Science, who collaborated tirelessly in crafting this book.